PERLINDUNGAN HUKUM TERHADAP ORANG DENGAN PENANGKAPAN KEKERASAN BERDASARKAN SISTEM HUKUM ACARA PIDANA - Sofianti, Adela Iragil; Zulkarnain, Zulkarnain (Universitas Muhammadiyah Ponorogo, 2024)
This study is a type of normative legal research that aims to determine how the legal protection against the violent arrest of Saipul Jamil by the police is based on the criminal procedure law system and how the police are legally responsible for the violent arrest carried out on Saiful Jamil. The results of this study indicate that the arrest process carried out by the Tambora police against Saipul Jamil is an action that violates the provisions and procedures for arrest and detention at the stage of criminal investigation as regulated in Perkap No. 12 of 2009 concerning supervision and control of the handling of criminal cases within the Indonesian National Police, one of which is that the arrest process does not include the type of arrest resulting from a sting or arrest for suspect status as regulated in article 77. In addition, the arrest process was not based on sufficient evidence, the identity of a clear task order letter and the use of violence in the arrest, thus clarifying that the arrest process carried out violated the provisions of the law and resulted in moral losses for Saipul Jamil. Therefore, due to the loss and the arrest process that did not comply with the procedures set out by law, Saipul Jamil has the right to claim compensation for the arrest process against him, as regulated in Article 23 of the Criminal Procedure Code which states that compensation can be implemented if a person's right to obtain restoration of his rights in his ability, position and dignity is granted at the level of investigation, prosecution or trial because he was arrested, detained, charged or tried without a reason based on law.